On weak solutions of the equations of motion of a viscoelastic medium with variable boundary. (13th November 2005) - Zvyagin, V. G.; Orlov, V. P.
Abstract : The regularized system of equations for one model of a viscoelastic medium with memory along trajectories of the field of velocities is under consideration. The case of a changing domain is studied. We investigate the weak solvability of an initial boundary value problem for this system.